2020
DOI: 10.21500/20112084.4078
|View full text |Cite
|
Sign up to set email alerts
|

Negative Emotions in Skin Disorders: A Systematic Review

Abstract: The main purpose of this study is to describe how negative emotions were investigated in the sphere of dermatological diseases, in order (1) to summarize literature trends about skin disorders and emotions, (2) to highlight any imbalances between the most studied and neglected emotions, (3) and to offer directions for future research. A computerized literature search provided 41 relevant and potentially eligible studies. Results showed that the study of emotions in skin disease is limited to Sadness/depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…1 Cumulatively, these phenomena highlight the adverse and cyclical effect that living with a skin condition can have on an individual's mood and physiological wellbeing. 4 Furthermore, these experiences often result in individuals adapting their behaviours and lifestyle, such as deploying avoidancebased coping, which can further perpetuate mental health difficulties. 5 Currently there are only a small number of in-depth large-scale qualitative studies that have sought to describe the range of psychosocial experiences of those living in the UK with skin conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Cumulatively, these phenomena highlight the adverse and cyclical effect that living with a skin condition can have on an individual's mood and physiological wellbeing. 4 Furthermore, these experiences often result in individuals adapting their behaviours and lifestyle, such as deploying avoidancebased coping, which can further perpetuate mental health difficulties. 5 Currently there are only a small number of in-depth large-scale qualitative studies that have sought to describe the range of psychosocial experiences of those living in the UK with skin conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that psychological distress can affect the perceived physical severity of a variety of skin disorders 1 . Cumulatively, these phenomena highlight the adverse and cyclical effect that living with a skin condition can have on an individual’s mood and physiological wellbeing 4 . Furthermore, these experiences often result in individuals adapting their behaviours and lifestyle, such as deploying avoidance‐based coping, which can further perpetuate mental health difficulties 5 …”
Section: Introductionmentioning
confidence: 99%
“…Also, in pemphigus vulgaris, another debilitating autoimmune condition, various clinical trials have concluded that there was higher mucocutaneous involvement in patients with higher depression levels. These findings emphasize the possible role of the effectiveness of mindfulness meditation in reducing the stress, pain, anxiety, and quality of life in such patients [ 22 ].…”
Section: Application Of Mbi For Psychosomatic Conditions and For Spec...mentioning
confidence: 79%
“…Broken skin (skin that has fissures, cracks, bleeds etc. ), such as in ichthyosis, may elicit disgust (Clarke, Thompson, & Norman, 2020 ), a concept that is understudied in research in the dermatologic field (Mento, Rizzo, Muscatello, Zoccali, & Bruno, 2020 ). Within clinical care, healthcare professionals may not feel confident in exploring this topic with parents or individuals with skin disorders such as ichthyosis.…”
Section: Discussionmentioning
confidence: 99%